2021
DOI: 10.3390/microorganisms9061123
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Genome Analysis Reveals Host-Specific Functional Divergences in Burkholderia gladioli

Abstract: Burkholderia gladioli has high versatility and adaptability to various ecological niches. Here, we constructed a pan-genome using 14 genome sequences of B. gladioli, which originate from different niches, including gladiolus, rice, humans, and nature. Functional roles of core and niche-associated genomes were investigated by pathway enrichment analyses. Consequently, we inferred the uniquely important role of niche-associated genomes in (1) selenium availability during competition with gladiolus host; (2) arom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 153 publications
1
8
0
Order By: Relevance
“…Considering the open state of the Campylobacter pan-genome, the results of the COG enrichment analysis of Campylobacter accessory genes and unique genes, especially “amino acid transport and metabolism” (E), “replication, recombination, and repair” (L), “cell wall/membrane/envelope biogenesis” (M), and “inorganic ion transport and metabolism” (P) ( Fig. 1c ), were consistent with the perspective that larger genomes tend to accumulate functions to enable organisms to achieve a higher degree of ecological diversification ( 31 ). In addition, the virulence-associated functional categories, such as the functional categories of “cell motility” (N), “inorganic ion transport and metabolism” (P), “signal transduction mechanisms” (T), and “defense mechanisms” (V) ( 32 , 33 ), were prominently represented in the variable component of the pan-genome, which might contribute to Campylobacter pathogenicity.…”
Section: Resultssupporting
confidence: 73%
“…Considering the open state of the Campylobacter pan-genome, the results of the COG enrichment analysis of Campylobacter accessory genes and unique genes, especially “amino acid transport and metabolism” (E), “replication, recombination, and repair” (L), “cell wall/membrane/envelope biogenesis” (M), and “inorganic ion transport and metabolism” (P) ( Fig. 1c ), were consistent with the perspective that larger genomes tend to accumulate functions to enable organisms to achieve a higher degree of ecological diversification ( 31 ). In addition, the virulence-associated functional categories, such as the functional categories of “cell motility” (N), “inorganic ion transport and metabolism” (P), “signal transduction mechanisms” (T), and “defense mechanisms” (V) ( 32 , 33 ), were prominently represented in the variable component of the pan-genome, which might contribute to Campylobacter pathogenicity.…”
Section: Resultssupporting
confidence: 73%
“…The divergence of species could result from a series of functional differentiation of genomes. In the field of molecular biology, accessory genes and unique genes are considered to have crucial influence on genome evolution and on the interplay between the environment and the genome, being further involved in functional diversification [ 43 , 44 ]. On the basis of the ideas described above, our study illuminated the functional diversity of bacterial strains in Gilliamella and Snodgrassella based on pan-genome analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Family Burkholderiaceae is characterized by the presence of ecologically extremely diverse organisms and contains truly environmental saprophytic organisms, phytopathogens, opportunistic pathogens, as well as primary pathogens for humans and animals [44]. B. gladioli was initially known as a plant pathogen, but currently, B. gladioli is isolated not only from plants [45], but also found in diverse habitats, including soil, environmental water [46,47], and even the respiratory tract of immunosuppressed humans [48,49]. Studies have shown that B. gladioli often symbioses with fungi and plants as well [50].…”
Section: Ficus Hirta Figs Microbial Compositionmentioning
confidence: 99%